Policy experimentation and impact evaluation: The case of a student voucher system in New Zealand - Sholeh A. Maani (Institute of Labor Economics (IZA), 2017)
While economic and political ideologies play an important role in the design of economic policies, in practice and regardless of ideology, the policies that stand the test of time are those that suitably meet policy objectives. The deregulation of schools in New Zealand, also known as Tomorrow's Schools, has drawn significant international attention due to its pioneering nature (following Sweden), and its history. In this paper the deregulation of schools in New Zealand since the 1990s is discussed to examine the role of policy outcomes and evaluations in continued policy design. The analysis in the paper highlights the significance of policy evaluations in guiding policy-retention and fine-tuning.
Keywords: I20; I21; I28; I24; 330; policy evaluation; student voucher system; Tomorrow's Schools; hybrid policies